Kemampuan Berpikir Kritis Mahasiswa Pendidikan Bilogi pada Materi Perubahan Lingkungan - Suryanti, Suryanti; Ferazona, Sepita; Praguna, Edo (UIR Press, 2025)
This research aims to determine the critical thinking abilities of biology education students on environmental change material, methodology using qualitative differentiation. The population in this research was Biology students in semesters III, V, totaling 57 people. Using a Saturated Sample considering that all of these students have taken Environmental Science courses. This research uses a type of primary data, namely tests, where the thinking test questions focus on environmental change material. Then carry out a Construct and Content Test by colleagues, there are 5 indicators where all 38 questions consist of 28 objective questions and 10 essay questions. After carrying out empirical tests and continuing with Reliability Tests using a Cronbach's Alpha value of 0.768. After empirical testing, there are 24 questions that can be used in data collection, including 17 objectives and 7 essays. Research data obtained from indicator one Providing a Simple Explanation, percentage 60.29 in the medium category, indicator two Building Basic Skills, percentage 56.2 in the low category, indicator three Drawing conclusions, percentage 61.12 in the medium category, Indicator four Providing further explanation, percentage 53.21 low category, indicator five Managing Strategy and Tactical 58.55 medium category. It can be concluded that the Critical Thinking Ability of Biology Education Students in Environmental Change Material is in the medium category.